Exploring Self-regulated learning Among Indonesian Undergraduates: A Focus on Metacognition, Motivation, and Behavior - Polla, Rina; Rahima, Amel Ghina (Indonesian Scientific Publication, 2025)
Higher education requires students to have strong self-regulated learning (SRL) abilities, which encompass metacognition, motivation, and learning behavior. This study aimed to describe the SRL levels of university students in Bandung City across these three core aspects. Using a quantitative approach with a cross-sectional survey design, data were collected from 235 active students from various universities through the SRL scale developed from Zimmerman’s (2000) model and adapted by Gabriela Devi Aninditya (2019). The findings revealed that the majority of students were in the moderate category on all three aspects, with motivation emerging as the lowest component (only 12.3% in the high category). These results indicate that while students generally have sufficient skills in planning and monitoring their learning, internal drive and motivational regulation remain key challenges. This highlights the need for interventions that strengthen motivation to support students’ independent learning and long-term academic success. By presenting a comprehensive profile of SRL across its main dimensions, this study provides empirical insights that can inform the development of educational programs and strategies in higher education.